The impact of bilinguality and language context on the understanding of epistemic adverbs in health communication: the case of English and Russian - Nissen, Vanda; Meuter, Renata F. I. (Frontiers in Psychology, 2023)
Objective: To explore differences, if any, in how English epistemic adverbs used in health communication are understood by speakers depending on their first language (Russian or English) and language context (resident in Australia or Russia). Methods: We used a dissimilarity rating task with sentence pairs, presented in online survey as first and second doctor opinions, which differed only with respect to the embedded epistemic adverbs (e.g., This treatment definitely has side effects vs. This treatment .possibly has side effects). To evaluate the possible effect of one’s first language, we compared the dissimilarity ratings of Australian monolinguals and Russian-English bilinguals in Australia (Study 1). To evaluate the impact of language context, we compared the dissimilarity ratings of Russian-English bilinguals in Australia and Russia (Study 2). The data were interpreted using classical MDS (C-MDS) analysis, complemented by cultural consensus analysis and hierarchical cluster analysis. Results: C-MDS analysis returned statistically acceptable results. The intragroup consensus was evident for all groups. While participants in both bilingual groups and the Australian monolingual group showed similarities in clustering the high confidence adverbs (clearly, definitely, and obviously) and hearsay adverbs (presumably and supposedly), the effect of first language (Russian or English) was noticeable (Study 1). Thus, Australian monolinguals included evidently in the group of high confidence adverbs. In our Study 2 effect of context was evident when Russian-English bilinguals in Australia showed more similarities in clustering epistemic adverbs to Australian monolinguals than to Russian-English bilinguals in Russia. For example, while Russian-English bilinguals and Australian monolinguals placed likelihood adverbs likely and possibly together, Russian-English bilinguals in Russia also added certainly to this cluster, showing less nuanced understanding of epistemic adverbs. Conclusions: While there were similarities in clustering the high confidence adverbs across three groups, there were also differences in clustering adverbs of likelihood and doubt between monolingual Australian English speakers and both groups of Russian-English bilingual speakers suggesting that there may be differences in comprehension of these adverbs in health communication. This may have implications for health practitioners who need to convey different degrees of risk and uncertainty to their CALD patients.